Exploration and research on reform and practice of graduation design for civil engineering major based on BIM technology and OBE concept - Yang, Rongzhou (Archives of Civil Engineering, 2026)
With the continuous development and progress of the construction industry, the requirements for civil engineering professionals are also increasing daily. Building a high-quality ability training model is the top priority in educational reform and development. As an important part of undergraduate teaching in civil engineering, graduation design plays a vital role in cultivating students' comprehensive abilities and innovative spirit. This research combined BIM technology with the OBE concept to conduct reform and practical research on graduation design for civil engineering majors. By analyzing the problems existing in the current graduation design of civil engineering majors, the advantages of BIM technology and the OBE concept and the necessity of combining the two were elaborated. This paper introduced in detail the graduation design reform plan based on BIM technology and the OBE concept, including reform measures in aspects such as design content, guidance methods, and evaluation system. Through actual case analysis and questionnaire survey, the effectiveness of the reform plan was verified and future development was prospected.